An Oligosilsesquioxane Cage Functionalized with Molybdenum(II) Organometallic Fragments - Dias Filho, Newton L. [UNESP]; Portugal, Fatima C. M.; Nogueira, J. M. F.; Brandao, Paula; Felix, Vitor; Vaz, Pedro D.; Nunes, Carla D.; Veiros, Luis F.; Villa de Brito, Maria J.; Calhorda, Maria Jose (Amer Chemical Soc, 2012)
A silsesquioxane cage polymer functionalized with eight chloropropyl arms (1, T-8-PrCl) reacted with 2,2'-dipyridiylamine (DPA) to afford a new derivative with eight pendant linear chains (2, T-8-Pr-DPA). Further reaction with [Mo(eta(3)-C3H5)Br(CO)(2)(NCMe)(2)] afforded another derivative containing three molybdenum units (3, T-8-Pr-DPA-Mo), after substitution of the two nitrite ligands in each complex. These are the first silsesquioxane species containing DPA and the Mo(eta(3)-C3H5)Br(CO)(2) fragment. The three materials were characterized by H-1, C-13, Si-29, and Mo-95 NMR, FTIR, XRD, and elemental analysis, and T-8-PrCl (1) was also structurally characterized by single-crystal X-ray diffraction. It was identified as a low-temperature polymorph of this material. Elemental analysis indicated that all Cl atoms in the parent material T-8-PrCl (1) were substituted by the deprotonated DPA group in T-8-Pr-DPA (2). However, only three [Mo(eta(3)-C3H5)Br(CO)(2)(DPA)] units were detected in T-8-Pr-DPA-Mo (3). A comprehensive NMR study, complemented with DFT calculations, was carried out in order to detect the effect of Mo coordination on the cage silicon and on the protons and carbons of the propyl chain, but no significant effects were observed. Both H-1 and Si-29 chemical shifts vary upon introducing DPA but remain the same after reaction with the Mo(II) precursor. The Mo-95 NMR data reveal that the metal is not sensitive to the cage. The catalytic activity of 3 was tested as a precursor in the epoxidation of cyclooctene and styrene in the presence of TBHP. Despite the high selectivity toward the epoxides, the conversion and turnover frequencies were low, reflecting the behavior of the [Mo(eta(3)-C3H5)Br(CO),(DPA)] complex.